A multiplicity result for some nonlocal eigenvalue problem with exponential growth condition. (September 2015) - Aouaoui, Sami
Abstract: In this paper, a new variational tool is used to establish a multiplicity result for some equation containing a nonlocal term and involving the N -Laplacian operator and whose nonlinear term can have a critical exponential growth. The equation has a nonvariational nature.